Government activity and economic growth: One size fits all? - Joscha Beckmann; Marek Endrich; Rainer Schweickert (Kiel Institute for the World Economy (IfW), 2014)
This study investigates the role of government activity in economic growth, arguing that economic systems are important and that, therefore, one size of government does not fit all countries. Taking a panel of 111 countries over the years from 1971 to 2010, we consider clusters of economic systems as predicted by an extended Varieties of Capitalism (VoC) approach. The empirical growth impact of government activity is positive but u-shaped and depends on both the quality of institutions and the institutional setting. For the polar cases of liberal economies and Scandinavian coordinated market economies, the potential growth impact is quite similar and superior to other clusters of countries. However, the maximum growth effect is realized for above-average levels of government activity in the Scandinavian countries, while this would be detrimental to growth in liberal countries. Hence, high levels of government activity are consistent with growth but only in economic systems consistently rooted in a high level of government activity.
Keywords: H10; P10; P51; 330; government spending; regulation; economic growth; economic systems; institutions